PENGARUH PEMBERIAN LAYANAN PESAN SINGKAT SEBAGAI PENGINGAT DAN MOTIVASI TERHADAP KUALITAS HIDUP PASIEN DIABETES MELITUS TIPE 2 DENGAN TERAPI ANTIDIABETIK ORAL - Baiq Leny Nopitasari; Wirawan Adikusuma; GJ Rahma Dewi Asamuni (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Diabetes Mellitus is a disease characterized by the occurrence of hyperglycemia (high blood sugar levels). Quality of life is one of the goals of DM management therapy so that further research is needed. This study aims to determine the effect of short message service as a reminder and motivation on the quality of life in supporting the success of DM Type 2 patients. This study uses quasi-experimental design by taking prospective patient data during the period July - August 2017. The subject of this study 60 patients with type 2 DM were divided into two groups: control group of 30 patients and treatment group of 30 patients. The data were collected by conducting interviews and filling out the SF-36 questionnaire to measure the quality of life. The SF 36 questionnaire has 8 domains where all domains have significant differences (P <0.05) before and after treatment. The quality of life of patients in the control and treatment groups had significant differences (P <0.05), in which the quality of life of patients in the treatment group was better than the quality of life in the control group. So the provision of short message service as a reminder and motivation can improve the quality of life of patients with type 2 diabetes mellitus.